STRUKTUR KOMUNITAS PLANKTON PADA TIGA ZONA DENGAN VARIASI SALINITAS DI LABUAN CERMIN KECAMATAN BIDUK-BIDUK, KAB. BERAU, KALIMANTAN TIMUR - B, Dian Aspiyani; Hariani, Nova; Hendra, Medi (Jurnal Pendidikan Matematika dan IPA, 2018)
The aim of this study is to know about the quality of the waters from the structure of community and level of diversity plankton on three zones vertically with variety salinity on labuan cermin, at Biduk-biduk, Kalimantan Timur. The sample is taken by used method purposive sampling. The data acquired and showed in profusion plankton form, index abundance, index diversity, index evenness, and index dominance. The plankton has found during the research is 79 genera classified in 46 family and 13 class. The index abundant is on station A is the highest than the other station. On the average of index diversity of station A higher than station B and C in value about 2,3026. Index evenness revolve from 0,1870 to 0,8281. Index dominance revolve about 0,1171 to 0,7885. Keywords: Estuary, plankton, Labuan Cermin, diversity.